UTILIZATION OF FLY ASH FROM PLTU KETAPANG AS FILLER ON HOT ROLLED SHEET (HRS-Base) - Juanda, Rizky Hendarta; Azwansyah, Heri; Kadarini, S. Nurlaily; Erwan, Komala (Jurnal Teknik Sipil, 2022)
The utilization of stone dust waste produced from PLTU Ketapang coal combustion process is still below optimal level. Produced waste reached ± 23,13 ton /day which consists of 99,5% of fly ash and 0,5% bottom ash. As a result, the writer gained an idea of using fly ash as a filler in bitumen mixture, especially in Hot Rolled Sheet   "“ BASE (HRS "“ BASE). The study was aimed to compare fly ash and stone dust if used as filler in Hot Rolled Sheet  "“ BASE (HRS "“ BASE) mix in marshall test including void analysis which consistsed of VMA, VIM, VFB, and MQ. The planned test item concentration of tar was on the level of 6%, 6,5%, 7%, 7,5%, and 8%.  The mixture which used stone dust as filler resulted in optimum bitumen content of 6,90% and the result of marshall test diplayed 912,072 kg of stability, 3,333 mm flow, 4,306%   VIM, 18,018 % VMA, 82,681% VFB, and 273,745 kg/mm MQ.    In the mixture which used fly ash as the filler resulted in optimum bitumen content of 7,1% with the marshall test displayed 877,132 kg of stability, 3,433 flow, 3,985% of VIM, 18,150% VFB, and the Marshall Quotient (MQ) 255,716 kg/mm.